The concept of poetry in the poems of Sherko Bekas (Raparin Journal of Humanities (RJH), 2023)
This research works on the concept of poetry, so the concept and definition of poetry have been discussed in general according to different stages, but in particular the concept of poetry has been worked on and introduced by Sherko Bekas, and this introduction is the first text. Poems that talk about the concept and recognition of poetry in all the poet's divans have become the material of the study, in order to present the opinion and definition of poetry from the poet's point of view, along with bringing back the poet's view of poetry in the dialogues with him, later comparing them, for the purpose of uniting, or having differences in their opinions.